2010 IEEE 12th Workshop on Control and Modeling for Power Electronics (COMPEL) 2010
DOI: 10.1109/compel.2010.5562432
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of an exponential adaptive perturb and observe algorithm and ripple correlation control for real-time optimization

Abstract: This paper proposes an exponential adaptive perturb and observe algorithm (EAPO) for real-time optimization of dynamic systems. Other adaptive methods are reviewed, and the mathematical formulation of the proposed EAPO is presented. Convergence and stability are discussed. Design requirements for applying EAPO are also addressed in an example for impedance matching. The proposed EAPO is compared to two prior realtime optimization techniques: conventional perturb and observe algorithm (P&O), and ripple correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The performance and comparison between these two methods had been carried out by [15], who concluded that the transient response of P&O is better than HC. The comparison between P&O with other methods also had been carried out by [31][32][33][34][35]. Principally, the operation of P&O or hill climbing technique is fully based on the perturbation or shifting of solar PV operation point according to the sign of the last increment of PV power.…”
Section: Photovoltaic Cell Modellingmentioning
confidence: 99%
“…The performance and comparison between these two methods had been carried out by [15], who concluded that the transient response of P&O is better than HC. The comparison between P&O with other methods also had been carried out by [31][32][33][34][35]. Principally, the operation of P&O or hill climbing technique is fully based on the perturbation or shifting of solar PV operation point according to the sign of the last increment of PV power.…”
Section: Photovoltaic Cell Modellingmentioning
confidence: 99%